Multiwavelength survey of a sample of flat-spectrum radio-loud narrow-line Seyfert 1 galaxies - Foschini, Luigi (2015)
We report on a multiwavelength survey of a sample of 42 flat-spectrum radio-loud narrow-line Seyfert 1 galaxies (RLNLS1s). This is the largest known sample of this type of active galactic nucleus (AGN) to date. We found that 17% of sources were detected at high-energy gamma rays (E > 100 MeV), and 90% at X-rays (0:3 - 10 keV). The masses of the central black holes are in the range ∼ 10⁶⁻⁸M⊙ , smaller than the values of blazars. The disk luminosities are about 1 - 49% of the Eddington value, with one outlier at 0.3%, comparable with the luminosities observed in flat-spectrum radio quasars (FSRQs). The jet powers are ∼ 10⁴²⁻⁴⁶ erg s⁻¹, comparable with BL Lac Objects, yet relatively smaller than FSRQs. However, once renormalized by the mass of the central black hole, the jet powers of RLNLS1s, BL Lacs, and FSRQs are consistent each other, indicating the scalability of the jets. We found episodes of extreme variability at high energies on time scales of hours. In some cases, dramatic spectral and flux changes are interpreted as the interplay between the relativistic jet and the accretion disk. We conclude that, despite the distinct observational properties, the central engines of RLNLS1s are similar to those of blazars.